2020
DOI: 10.3390/nu12051385
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Its Determinants in a Paediatric Population in Norway

Abstract: Recommendations for sufficient vitamin D intake in children were recently revised in Norway. However, optimal levels of vitamin D are still debated and knowledge on supplementation and vitamin D levels in healthy children in Norway is scarce. Therefore, we measured the plasma-concentration of 25-hydroxyvitamin D (25(OH)D) in children and adolescents attending the outpatient paediatric clinics in Innlandet Hospital Trust, Norway during two consecutive years (2015–2017). We recruited 301 children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…Our study demonstrated that 25(OH)D levels in students and adults aged 24–60 years were higher than in school age children. This is consistent with earlier published findings [25,30] and may be explained by the end of body growth and a more conscious approach to food choices. Nevertheless, only a quarter of adults in the study had normal levels of vitamin D.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study demonstrated that 25(OH)D levels in students and adults aged 24–60 years were higher than in school age children. This is consistent with earlier published findings [25,30] and may be explained by the end of body growth and a more conscious approach to food choices. Nevertheless, only a quarter of adults in the study had normal levels of vitamin D.…”
Section: Discussionsupporting
confidence: 93%
“…The results demonstrate low levels of vitamin D in the Arkhangelsk population living at 64° N. These findings are in line with the results of studies in other northern countries such as Norway and Sweden [13,14,24,25]. The lowest concentrations of 25(OH)D were found in neonates, which is consistent with findings in earlier international research [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, young children tend to spend more time outdoors, benefiting from sun exposure, often with parental supervision. One Norwegian study that was published in 2020 and included in this mini review indicated that nearly 62% of young children, particularly those under 2 years old, were given vitamin D supplements 10 . This percentage was significantly higher than a previous nationwide dietary survey among Norwegian schoolchildren, conducted in 2015, where less than half reported taking vitamin D supplements 25…”
Section: Discussionmentioning
confidence: 90%
“…The headline findings from the six Norwegian papers included in this mini review were that adolescents faced a higher risk of insufficient vitamin D levels and so did children with a non‐Western immigrant background (Table 1). 8–13 A study of a healthy paediatric population, published in 2020, reported that 78% of the participants had ample 25(OH)D levels (>50 nmol/L), while 1% were deficient and 21% had inadequate levels 10 . The 1% that were deficient were all adolescents 10 .…”
Section: Resultsmentioning
confidence: 99%